IMPLEMENTATION OF FOOD RESERVE REGULATION IN SUMENEP DISTRICT - Nur Hayat; V. Rudy Handoko; Achluddin Ibnu Rochim (DIA: Jurnal Administrasi Publik, 2026)
This study evaluates the implementation of regional regulations on food reserves in Sumenep Regency to strengthen local food security. The regulation aims to manage food reserves, stabilize supply, and address potential food crises caused by natural disasters or price fluctuations. This research examines the application of the policy and factors influencing its success or failure. A descriptive qualitative method was employed, collecting data through in-depth interviews with local government officials, farmers, and beneficiaries. Field observations and document analysis complemented the interviews. The findings reveal that while the regulation was implemented to enhance food security, challenges remain, including budget constraints due to COVID-19 and Foot-and-Mouth Disease, limited inter-agency coordination, and low community participation. Technical issues, such as inadequate storage and distribution facilities, further hinder implementation. However, positive factors include government commitment, human resource development, and active community and private sector involvement. The study recommends improving stakeholder collaboration and strengthening monitoring and evaluation systems to ensure effective and sustainable food reserve policies in the future.